(untitled) (Journal of Naval Architecture and Marine Engineering, 2019)
Sustainable power generation, energy security, and global warming are the big challenges to the world today. These issues may be addressed through the increased usage of renewable energy resources and concentrated solar energy can play a vital role in this regard. The performance of a parabolic-trough collector’s receiver is here investigated analytically and experimentally using water based and therminol-VP1based CuO, ZnO, Al2O3, TiO2, Cu, Al, and SiC nanofluids. The receiver size has been optimized by a simulation program written in MATLAB. Thus, numerical results have been validated by experimental outcomes under same conditions using the same nanofluids. Increased volumetric concentrations of nanoparticle is found to enhance heat transfer, with heat transfer coefficient the maximum in W-Cu and VP1-SiC, the minimum in W-TiO2 and VP1-ZnO at 0.8 kg/s flow rate. Changing the mass flow rate also affects heat transfer coefficient. It has been observed that heat transfer coefficient reaches its maximum of 23.30% with SiC-water and 23.51% with VP1-SiC when mass-flow rate is increased in laminar flow. Heat transfer enhancement drops during transitions of flow from laminar to turbulent. The maximum heat transfer enhancements of 9.49% and 10.14% were achieved with Cu-water and VP1-SiC nanofluids during turbulent flow. The heat transfer enhancements of nanofluids seem to remain constant when compared with base fluids during either laminar flow or turbulent flow.